A Comparison of Basti Instruments Used in Samhita and Current Period with special reference to Mode of Action - D, Anusree; Vedpathak, Surendra (International Research Journal of Ayurveda & Yoga, 2022)
multifaceted action. Basti is considered to be the best therapy, also known as “Ardha Chikitsa” as well as “Poorna Chikitsa” because it is not only having curative action, but also preventive and promotive actions. Basti is a complex, but systematic procedure having wide therapeutic potency. Basti Sammelana is a unique series of steps which also contributes to the mode of action of Basti. This process is especially told for Nirooha type of Basti, where there is a combination of drugs present. Different Acharyas has given a wide set of instruments in Basti Sammelana, but in the current scenario modifications has been done with the advanced technology. In administration of Basti karma, owing to the practicality time to time changes has been incorporated. Here, an effort has made to compile and critically analyse the different instruments used in the Basti Sammelana and administration of Basti.